Flashover performance of lightning protected buildings using scaled models and electric field analysis - Ullah, Irshad (2018)
In early era, Benjamin Franklin discovered that the application of Lightning Rod (also known as the Franklin Rod) method is found to be effectived as a lightning protective device for buildings. Hence, it was considered among the best solution to overcome the problems facing by publics due to lightning strikes. However, few years later it was found that the corroded Franklin Rod due to the impact of environmental contaminations tends to reduce its ability to effectively capture the lightning strikes. The directly or indirectly impacts of lightning strikes had caused owners to spend huge amount of money just to repair damages on the buildings. Nowadays, there were many professional standards and documents guiding public to properly install the building’s lightning protection system, yet the same damages problems had shown to be frequently occur that related to the strikes often bypasses the of Lightning Air Terminal (LAT) system. The main reason for this could be due to lacking ideas by learned circle of lightning experts as not to fully understand the behavior of Franklin Rods system when it interacts with the lightning leaders. Therefore, this thesis discusses the works that investigated the flashover performances occurred on the buildings with various structural geometry shapes. The case study method is using small scaled models for both laboratory and simulation works, aiming to understand the Franklin Rods performance on capturing lightning leaders. Summarizing the works, about 11 scaled-down building shape models equipped with Franklin Rods system are selected in the case studies such as follows; a conical, gable, triangular, half circle, L-shape, square, cylindrical, butterfly, pyramid, rectangular and inclined like shapes. These models were then injected with 30 lightning flashes each using the 100 kVpeak single stage impulse generator. This number of flashes is considered as total two-years lightning activity frequencies in Malaysia, which the lighting flash density is statistically recorded to be around 15 flashes / year / km2. The maximum applied voltage is about 86.5 kVpeak. The model scaling concept is based on 1:30 cm ratio for every 3 m height of building structure. Interestingly, the overall work data had shown that the pyramid-like shapes is found to be the best structure type to be used in reducing the LAT bypasses and direct strike damages. The structure’s Franklin Rod protection system captured the least number of strikes during competitive tests conducted on all of the scaled down building models. Works of electric field analysis on all building models were conducted using ANSYS Maxwell simulation tool. Utilisation of electric field plot data in this work enables the creation of likelihood factor (ranging from 0.1 to 0.9) method that so useful to capable predict the strikes pattern occurring on dedicated terminal rod. Both laboratory and simulation work also confirm that the edge shapes play crucial roles as intense electric fields is found to accumulate on the edges area when the Franklin Rod intercepts the lightning leaders. These mentioned findings lead to introducing better method of LAT placement on the top of the building, whereby the existing lightning protection system is recommended to have one of installed LAT rods elongated to act as sacrificial point to directly attract lightning strikes. All the work and key findings in this work can contribute to the science and technology field toward having a better LAT lightning protection system and also lead to better decision in selecting / designing the shapes and edges concept as to reduce likelihood of LAT bypasses and damages of the building structure.